Concordance study between regular face-to-face dental diagnosis and dental telediagnosis using fluorescence. (September 2021) - Inquimbert, Camille; Hirata-Tsuchiya, Shidu; Yoshii, Shinji; Molinari, Nicolas; Nogue, Erika; Roy, Clement; Morotomi, Takahiko; Washio, Ayako; Cuisinier, Frederic; Tassery, Herve; Levallois, Bernard; Kitamura, Chiaki; et al.
Background: Teledentistry consultations are an effective way to increase access to care. Whether it be for a screening, referral or even an adapted treatment plan for a certain number of patients whose access to care is complicated, demonstrating the reliability of remote consultations is essential in allowing the technique to become generalised. Aim: This study aimed to determine if teledentistry consultations using fluorescence are of the same quality as regular consultations in the diagnosis of caries. Methods: Patients were seen in consultation in the dental care centre at the Montpellier University Hospital (France) and in the centre at Kyushu Dental University Hospital (Japan). The protocol was broken down into three parts: the regular consultation, the recording of videos with the Soprocare camera and the remote consultation. The regular consultation and the remote consultation were blinded and carried out by two different dentists. The recording of videos was carried out by a third dentist. The carious diagnosis was based on the International Caries Detection and Assessment System: a clinical rating system for the detection and assessment of caries. Results: One hundred and ninety-five patients met the predefined inclusion criteria. Most patients had at least one surface at stage 3 or higher (73%) with a higher proportion amongst French patients (81% compared to 66%). However, they had good dental hygiene, given that dental hygiene was only deemed unsatisfactory for 10.8% (19% for French patients and 2% for Japanese patients). The odontogram (presence/absence of each tooth) seemed to be correctly identified during the remote consultation (reinterpretation). Out of the 195 patients, 168 (86.2%) were identified without error. Conclusions: Teledentistry consultations can represent acceptable diagnostic performance with regard to the detection of dental caries. The Soprocare camera enables an early diagnosis of carious lesions with optimal efficiency. Several areas still need to be improved, however, so that the use of the camera during remote consultations is as coherent and effective as possible, especially with regard to the organisational aspects of remote consultations.